2012
DOI: 10.1183/09031936.00059712
|View full text |Cite
|
Sign up to set email alerts
|

Use of continuous positive airway pressure reduces airway reactivity in adults with asthma

Abstract: Asthma is characterised by airway hyperreactivity, which is primarily treated with β-adrenergic bronchodilators and anti-inflammatory agents. However, mechanical strain during breathing is an important modulator of airway responsiveness and we have previously demonstrated in animal models that continuous positive airway pressure (CPAP) resulted in lower in vivo airway reactivity. We now evaluated whether using nocturnal CPAP decreased airway reactivity in clinically-stable adults with asthma. Adults with stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 30 publications
3
51
1
2
Order By: Relevance
“…Other studies of shorter treatment periods did not found any improvement 33. The relationship between OSAS, obesity, local airways inflammation, and bronchial hyperresponsiveness (BHR) has also been extensively studied, as well as the response after CPAP therapy 33, 34, 35, 36, 37, 38. In patients with asthma, a reduction in BHR has been reported in the majority of studies 34, 35.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies of shorter treatment periods did not found any improvement 33. The relationship between OSAS, obesity, local airways inflammation, and bronchial hyperresponsiveness (BHR) has also been extensively studied, as well as the response after CPAP therapy 33, 34, 35, 36, 37, 38. In patients with asthma, a reduction in BHR has been reported in the majority of studies 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between OSAS, obesity, local airways inflammation, and bronchial hyperresponsiveness (BHR) has also been extensively studied, as well as the response after CPAP therapy 33, 34, 35, 36, 37, 38. In patients with asthma, a reduction in BHR has been reported in the majority of studies 34, 35. By contrast, in nonasthmatic patients with OSAS, BHR frequently increases 33, 36, although not always 37.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations